Retraction Note: Clinical Application of Thyrotropin Receptor Antibodies - yang, Yang; weipeng, Huang (Hormone and Metabolic Research)
This article has been retracted by Thieme and the Editor in Chief. This article was published in error and this retraction is thus not the result of any fault or action of the authors. The Publisher and Editor apologise for this mistake and any inconvenience caused by this error.